2011
DOI: 10.1007/s11999-010-1653-5
|View full text |Cite
|
Sign up to set email alerts
|

Laminoplasty versus Laminectomy and Fusion for Multilevel Cervical Spondylotic Myelopathy

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 27 publications
7
100
0
1
Order By: Relevance
“…These studies were designed to compare the efficacy and complication rates between 2 different surgical interventions or varying techniques. Studies reported on differences between anterior and posterior approaches (n = 9); 15,18,19,22,30,42,44,48,59 laminoplasty and laminectomy and fusion (n = 4); 10,19,70,72 anterior decompression and Bryan disc (n = 1); 11 and anterior cervical discectomy and fusion (ACDF) and corpectomy (n = 2). 47,63 In addition, 11 studies compared laminoplasty techniques or considered technical differences such as laminoplasty with and without foraminotomy or muscle preservation.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These studies were designed to compare the efficacy and complication rates between 2 different surgical interventions or varying techniques. Studies reported on differences between anterior and posterior approaches (n = 9); 15,18,19,22,30,42,44,48,59 laminoplasty and laminectomy and fusion (n = 4); 10,19,70,72 anterior decompression and Bryan disc (n = 1); 11 and anterior cervical discectomy and fusion (ACDF) and corpectomy (n = 2). 47,63 In addition, 11 studies compared laminoplasty techniques or considered technical differences such as laminoplasty with and without foraminotomy or muscle preservation.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…17 The spinal cord in CSM is compressed because of the degeneration of intervertebral discs and the secondary degeneration of stable structures, such as the uncovertebral joint, facet joint, posterior longitudinal ligament, and ligamentum flavum. 4 Because compressive lesions leading to cervical myelopathy usually arise anteriorly, proponents of anterior surgery cite as advantages the ability to directly remove the majority of compressive lesions in the cervical spine, a muscle-sparing dissection, which results in minimal postoperative pain, and the ability to correct and decompress the cord over kyphotic lesions.…”
mentioning
confidence: 99%
“…Prior reports have documented rates of complications associated with the surgical treatment of CSM, [1][2][3][4][6][7][8]11,12,[14][15][16][18][19][20]31,33 but the data from these reports have key limitations, including retrospective design, [2][3][4]7,8,11,12,[14][15][16][18][19][20]31,33 reporting of a single-surgeon or single-institution experience, 1,2,4,7,8,11,12,14,16,18,19,31 and reliance solely on inpatient ICD-9 codes. 3 In addition, many of these prior reports are based on small numbers of patients, which may be inadequate to estimate rates of less common complications.…”
mentioning
confidence: 99%